A Aplikasi Pengenalan Koleksi Museum Dirgantara Mandala Yogyakarta Menggunakan Augmented Reality - Prihantoro, Wisnu; Aji, Adam Sekti (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
The Yogyakarta Mandala Aerospace Museum is a museum that contains historical collections, most of which are airplanes. This museum was previously located in Jakarta and was inaugurated on April 4, 1969, then moved to Yogyakarta on July 29, 1978. The Yogyakarta Mandala Dirgantara Museum documents all historical events in the growth of the Indonesian Air Force and contains the noble values of the 1945 struggle that can be passed on to the younger generation. At the moment. In designing and creating Augmanted Reality (AR) applications using the Marker Based method, markers as camera triggers to display 3D objects and relevant historical information are the aim of this research. This research is expected to produce an interactive and informative application for museum visitors and increase understanding of the historical collection of the Yogyakarta Mandala Dirgantara Museum..